Pengetahuan triase pada perawat di rumah sakit: A scoping review - Rahman, Lutfi; Trisyani, Yanny; Emaliyawati, Etika (Holistik Jurnal Kesehatan, 2025)
Background: Triage knowledge is an important aspect of nursing practice, particularly in hospital emergency departments (EDs). Effective triage can improve the quality of patient care and optimize health resources. However, there is a gap between the triage knowledge that nurses have and the practice applied in the field. Various studies have shown that although nurses have an understanding of triage theory, implementation in the field is often not optimal. This can affect the quality of health services and patient safety. Purpose: To explore the triage knowledge of nurses in hospitals and the challenges faced in its implementation. Method: A scoping review was conducted by searching articles from three databases, namely CINAHL, PubMed, and Scopus. The keywords used included “triage knowledge,” “nurses”, “hospitals”, and “triage practice”. Inclusion criteria included articles published in English that addressed nurses' triage knowledge in a hospital context. Data were extracted using manual tables, and data analysis was performed in a qualitative descriptive manner. Results: There were seven articles that met the inclusion criteria and addressed nurses' triage knowledge in hospitals. Results showed that although nurses have basic knowledge of triage, there are challenges in optimal implementation, such as the lack of use of standardized triage scales. Themes identified included improving knowledge through training, the influence of work experience, as well as the need for continuing education. Variables influencing triage knowledge included formal education, work experience, and type of training received. Conclusion: Triage knowledge in hospital nurses requires more attention in terms of continuing education and training. Further research is needed to explore strategies that can improve effective triage implementation in clinical practice. Suggestion: Future research could conduct more in-depth longitudinal studies to explore the impact of ongoing triage training on nurses' skills and practices in emergency situations, as well as to assess the effectiveness of using standardized triage scales across cultural contexts and health systems.   Keywords: Knowledge; Nurses; Triage.   Pendahuluan: Pengetahuan triase merupakan aspek penting dalam praktik keperawatan, khususnya di unit gawat darurat (UGD) rumah sakit. Triase yang efektif dapat meningkatkan kualitas perawatan pasien dan mengoptimalkan sumber daya kesehatan. Namun, terdapat kesenjangan antara pengetahuan triase yang dimiliki perawat dan praktik yang diterapkan di lapangan. Berbagai studi menunjukkan bahwa meskipun perawat memiliki pemahaman tentang teori triase, penerapan di lapangan sering kali tidak optimal. Hal ini dapat berpengaruh pada kualitas pelayanan kesehatan dan keselamatan pasien. Tujuan: Untuk mengeksplorasi pengetahuan triase pada perawat di rumah sakit dan tantangan yang dihadapi dalam implementasinya. Metode: Penelitian scoping review dilakukan dengan pencarian artikel dari tiga database, yaitu CINAHL, PubMed, dan Scopus. Kata kunci yang digunakan mencakup "pengetahuan triase", "perawat", "rumah sakit" dan "praktik triase". Kriteria inklusi meliputi artikel yang diterbitkan dalam bahasa Inggris dan membahas pengetahuan triase perawat dalam konteks rumah sakit. Data diekstraksi menggunakan tabel manual, dan analisis data dilakukan secara deskriptif kualitatif. Hasil: Terdapat tujuh artikel yang memenuhi kriteria inklusi dan membahas pengetahuan triase perawat di rumah sakit. Hasil menunjukkan bahwa meskipun perawat memiliki pengetahuan dasar tentang triase, terdapat tantangan dalam penerapan yang optimal, seperti kurangnya penggunaan skala triase terstandarisasi. Tema yang diidentifikasi meliputi peningkatan pengetahuan melalui pelatihan, pengaruh pengalaman kerja, serta kebutuhan akan pendidikan berkelanjutan. Variabel yang mempengaruhi pengetahuan triase termasuk pendidikan formal, pengalaman kerja, dan jenis pelatihan yang diterima. Simpulan: Pengetahuan triase pada perawat rumah sakit memerlukan perhatian lebih dalam hal pendidikan dan pelatihan berkelanjutan. Penelitian lebih lanjut diperlukan untuk mengeksplorasi strategi yang dapat meningkatkan penerapan triase yang efektif dalam praktik klinis. Saran: Penelitian selanjutnya dapat melakukan studi longitudinal yang lebih mendalam untuk mengeksplorasi pengaruh pelatihan triase berkelanjutan terhadap keterampilan dan praktik perawat dalam situasi darurat, serta untuk menilai efektivitas penggunaan skala triase terstandarisasi di berbagai konteks budaya dan sistem kesehatan.   Kata Kunci: Pengetahuan; Perawat; Triase.